Hybrid genesis of Jurassic fayalite-bearing felsic subvolcanic rocks in South China: Inspired by petrography, geochronology, and Sr–Nd–O–Hf isotopes - Guo, Chunli; Zeng, Lingsen; Li, Qiuli; Fu, Jianming; Ding, Tiping (Lithos, 2016)
Fayalite-bearing felsic (FBF) magmatic rocks are a special type of granitic rocks with controversial origins. A suite of fayalite- and ferrosilite-bearing subvolcanic rocks, namely, the Xishan FBF rocks in South China, is investigated in this study. The Xishan FBF rocks have high SiO2 contents of 69–70wt.%, high K2O/Na2O ratios of 1.71–1.95, and high FeOt/(FeOt+MgO) ratios of 0.88–0.89. Fayalite (Fo=7.3–9.6) and ferrosilite (Fs=74.1–76.5) minerals are found in the Xishan FBF rocks. According to the Unmix function of Isoplot, the zircon U–Pb ages and initial Hf isotope compositions are categorized into two groups with ages of 156.6Ma and 151.5Ma and εHf(t) values of −7.1 and −5.2, respectively. The minerals show δ18O values of 8.8–9.8‰ for zircon, 6.0–8.1‰ for fayalite, and 7.0–8.2‰ for ferrosilite. The oxygen isotope fractionations between ferrosilite and fayalite (ΔOpx-Ol) vary from −0.8‰ to +1.5‰, which indicates disequilibrium crystallization. Whole-rock analyses show high initial 87Sr/86Sr ratios of 0.7169 to 0.7180 and negative εNd(t) values of −7.3 to −6.8; zircon analyses show εHf(t) values of −9.1 to −3.8 and δ18O values of 8.8–9.8‰. So whole rock and zircon isotopes indicate a crustal signature. Based on these mineralogical and geochemical data, the Xishan FBF rocks were attributed to A-type granites and derived from the mixing of two batches of crustal magmas, which were all derived from the partial melting of ancient igneous protolith under the conditions of high temperature (683–893°C), moderate water (3–5wt.%), and low oxygen fugacity (lg fO2=−1.21). Such rigorous physical conditions may be common for the FBF igneous rocks all over the world, which may be the primary factors controlling occurrence of the FBF rocks in limited volume and quantity. •The Xishan fayalite-bearing subvolcanic rocks originated from the mixing of two batches of crustal magmas.•Two populations of zircon U-Pb ages and initial Hf isotope compositions distinguish these two magma pulses.•Non-equilibrium partitioning of oxygen isotopes had happened among zircon, fayalite, and ferrosilite.•All the fayalite-bearing felsic rocks worldwide formed under high temperature, low-moderate water, and low oxygen fugacity.•Aforementioned restricted physical conditions can explain the limited volumes of such rocks in nature.